PERENCANAAN RUANG TERBUKA HIJAU DI PERUMAHAN BRD RESIDENCE KOTA PEKALONGAN - Tisnawati Tisnawati; Dwi Kumalasari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2018)
Green Public Space is an open social facility where all people can use it. The green public space it self is functioned as a social facility, such as children's playground, place to relax, and a place to exercise, green public space can also be used as a water catchment area that can be used for reducing the occurrence of inundation and flooding. It is expected that the presence of green public space in the housing environment can improve the quality of the surrounding environment, as the identity of this housing, and can also be added value for BRD Residence housing. Designing a comfortable green public space for residents to visit in particular and residents of Pringrejo Village in general and to find out how much the budget plan is needed to build a green public space in the BRD Residence housing. From the results of the survey pad a measurement of the study location obtained a land area of 1148 m2 with a length of 82 m and a width of 14 m, while from the results of analysis, this green public space is a type of park RW. In calculating the budget plan for planning the green public space or park RW, the total cost needed for the construction of green public space is Rp 410.000.000,00 consisting of 5 jobs, including; paving work of Rp 91.618.355,55, playground work of Rp 67.983.960,74, jogging track Rp 45.031.556,25, gazebo work in the amount of Rp 151.351.789,08, and in the flower garden work of Rp 54,018,901.72.Keywords: Green Open Space, Planning, Costs.